Qinghai Lake Basin Critical Zone Observatory on the Qinghai‐Tibet Plateau. Issue 1 (9th August 2018) - Li, Xiaoyan; Yang, Xiaofan; Ma, Yujun; Hu, Guangrong; Hu, Xia; Wu, Xiuchen; Wang, Pei; Huang, Yongmei; Cui, Buli; Wei, Junqi
Abstract : Core Ideas: The QLBCZO is an observatory to study carbon–water processes on the Qinghai‐Tibet Plateau. Multiscale, multi‐interface, and multi‐process studies investigate the CZ in the alpine region. Models predict carbon sequestration and water resources in the Qinghai Lake Basin. The surface–subsurface architecture of the critical zone (CZ) regulates the hydrologic and geochemical processes that drive the CZ function. Due to the complex heterogeneity, highly coupled processes, and the dynamic controlling mechanisms across scales, CZ science faces grand challenges on interface coupling, process integration, and scaling. Carbon–water cycles are important physical‐geochemical processes in the CZ. However, the key factors that govern the carbon–water processes across spatiotemporal scales under natural conditions are poorly understood. Especially, such research in the CZ of the alpine region, e.g., the Qinghai‐Tibet Plateau (QTP), has not been reported yet is challenging to conduct. The Qinghai Lake Basin Critical Zone Observatory (QLBCZO) is being established to study alpine hydrology, carbon–water processes, and ecological functions on the northeastern QTP. Previous studies in the QLBCZO mainly focused on ecohydrologic processes and the water budget. Currently, the QLBCZO is designed to integrate state‐of the‐art observation techniques (such as including deep coring, ground‐penetrating radar, electrical resistance tomography, isotope technique, and remote sensing) and frontier modeling approaches to investigate: (i) the three‐dimensional architecture of the subsurface environment (vegetation–soil–rock–microbial community) as well as the carbon and water storage, (ii) multiscale carbon–water processes and carbon–water budget, (iii) interactions between freeze–thaw and carbon–water processes, and (iv) carbon sequestration and water resources. The establishment of the QLBCZO and its associated research would be crucial for advancing both theory and methodology for the CZ and Earth system science research on the QTP and alpine regions in general.